Strategy to Increase Market Share of Bank Syariah Indonesia (BSI) in North Sumatra Region - Anisa Pratiwi; Andri Soemitra; Ahmad Amin Dalimunte (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to find out how the top priority strategy for increasing BSI market share in North Sumatra by presenting internal and external conditions that have been carried out and discussed with experts. Then as an alternative to additional policies, the researcher also explained some of the urgency of handling that needs to be applied so that market share development can be directed. The method used is a SWOT analysis. there were seven respondents who filled out their respective questionnaires. Based on the results of the SWOT analysis, the quadrant of strategies obtained after being processed in the IFAS and EFAS matrices is a defensive strategy. This strategy means that it is necessary to minimize weaknesses and avoid threats. The results obtained from the SWOT analysis can be read with a SWOT quadrant that shows the Diversification strategy contained in the ST (Strength – Threat) strategy. Penelitian ini bertujuan untuk mengetahui bagaimana strategi prioritas utama peningkatan pangsa pasar BSI di Sumatera Utara dengan menghadirkan kondisi internal dan eksternal yang telah dilakukan dan didiskusikan dengan para ahli. Kemudian sebagai alternatif kebijakan tambahan, peneliti juga menjelaskan beberapa urgensi penanganan yang perlu diterapkan agar pengembangan pangsa pasar dapat diarahkan. Metode yang digunakan adalah analisis SWOT. ada tujuh responden yang mengisi kuesioner masing-masing. Berdasarkan hasil analisis SWOT, kuadran strategi yang diperoleh setelah diproses dalam matriks IFAS dan EFAS merupakan strategi defensif. Strategi ini berarti bahwa perlu untuk meminimalkan kelemahan dan menghindari ancaman. Hasil yang diperoleh dari analisis SWOT dapat dibaca dengan kuadran SWOT yang menunjukkan strategi Diversifikasi yang terdapat dalam strategi ST (Strength – Threat).